The Symbolic Relation Between Human and Nature in Palembang Traditional Marriage of Suap-Suapan and Cacap-Cacapan - Tazami Jeni Arasyita (EDP Sciences, 2021)
Palembang's traditional marriage ceremonies, which are to be studied here, are suap-suapan and cacap-cacapan. The background of choosing this subject is to introduce the marriage ceremony back, which is lately being forgotten. The method used in this research is the qualitative method with an ethnographic communication approach. This study aimed to describe the ethnography of communication using Hymes theory. The results showed that the communicative situation of suap-suapan and cacap-cacapan happened after the solemnization of marriage had been done and took place in the groom house. The communicative events of suap-suapan and cacap-cacapan contain roasted chicken turmeric rice symbolized prosperity and grandeur. At the same time, fresh water in a bowl filled with setaman nature flowers symbolized the purity of the noble ideals of beauty and fragrance that blends in life. The communicative actions started with 1. Opening 2. Suap-suapan then followed by Cacap-cacapan. 3. Prayer, and 4. Closing. Suap-suapan and cacap-cacapan are some of the customs that contain traditional values. However, along with the development era, it is less noticed. Therefore, hopefully, this paper could be helpful to introduce this marriage ceremony back to be understood and lived until finally, it will evoke pride in the Palembang community towards its own culture.